1999
DOI: 10.1016/s1071-3581(99)90037-5
|View full text |Cite
|
Sign up to set email alerts
|

Interpretive reproducibility of stress Tc-99m sestamibi tomographic myocardial perfusion imaging

Abstract: There is moderate to excellent interpretive reproducibility with stress Tc-99m sestamibi SPECT imaging among nuclear cardiologists with a wide range of training and experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 20 publications
0
19
0
2
Order By: Relevance
“…These findings are consistent with other trials in which higher interobserver variability of stress echocardiography was reported compared to MPI. [43][44][45][46] The addition of automated quantitation software, not used in the current study but commonly in use today, would be expected to further reduce interobserver variability during SPECT MPI interpretation. [47][48][49] Interestingly, interobserver agreement between the same two primary DSE readers was substantially higher in a previous report where access to clinical data was identical to this study (78%, kappa = .55).…”
Section: Prognosismentioning
confidence: 99%
“…These findings are consistent with other trials in which higher interobserver variability of stress echocardiography was reported compared to MPI. [43][44][45][46] The addition of automated quantitation software, not used in the current study but commonly in use today, would be expected to further reduce interobserver variability during SPECT MPI interpretation. [47][48][49] Interestingly, interobserver agreement between the same two primary DSE readers was substantially higher in a previous report where access to clinical data was identical to this study (78%, kappa = .55).…”
Section: Prognosismentioning
confidence: 99%
“…The analysis often used sample-weighted averages to calculate agreement rates, which gives the category with the highest number of patients the greatest contribution to the average. Finally, agreement rates are usually reported for the overall impression of the scan as normal versus abnormal or normal versus ischemia versus infarct; it is well known that agreement rates are better when categories are narrow rather than wide, such as extent and severity of ischemia (7,8).…”
Section: Technical Issues In Image Interpretation Specific To Mpimentioning
confidence: 99%
“…Agreement between the initial interpretation of the global score and the blinded re-read four years later was good, with 82% concordance (K ϭ 0.68). This is comparable, though slightly less, than the concordance rates in the intraobserver reproducibility studies of Danias et al (24), 83% to 88% (K ϭ 0.54 to 0.73), and Golub et al (25), 88% to 93% (K ϭ 0.76 to 0.87).…”
Section: Discussionmentioning
confidence: 60%
“…The images interpreted for the study of Danias et al (24) were performed with the benefit of motion correction software, while such software was not available in the current study. In the study of Golub et al (25), only studies of "good-to-excellent" quality were selected for inclusion. As well, Golub et al (25) included only patients undergoing exercise stress, 16% of whom were women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation